Clinical and Laboratory Features of Human Plasmodium knowlesi Infection - Daneshvar, C.; Davis, T.M.E; Cox-Singh, J.; Mohammad Zakri, Rafa’ee; Siti Khatijah, Binti Zakaria; Paul C, Divis; Balbir, Singh (Infectious Diseases Society of America, 2009)
Background—Plasmodium knowlesi is increasingly recognized as a cause of human malaria in Southeast Asia but there are no detailed prospective clinical studies of naturally acquired infections. Methods—In a systematic study of the presentation and course of patients with acute P. knowlesi infection, clinical and laboratory data were collected from previously untreated, nonpregnant adults admitted to the hospital with polymerase chain reaction–confirmed acute malaria at Kapit Hospital (Sarawak, Malaysia) from July 2006 through February 2008. Results—Of 152 patients recruited, 107 (70%) had P. knowlesi infection, 24 (16%) had Plasmodium falciparum infection, and 21 (14%) had Plasmodium vivax. Patients with P. knowlesi infection presented with a nonspecific febrile illness, had a baseline median parasitemia value at hospital admission of 1387 parasites/μL (interquartile range, 6–222,570 parasites/μL), and all were thrombocytopenic at hospital admission or on the following day. Most (93.5%) of the patients with P. knowlesi infection had uncomplicated malaria that responded to chloroquine and primaquine treatment. Based on World Health Organization criteria for falciparum malaria, 7 patients with P. knowlesi infection (6.5%) had severe infections at hospital admission. The most frequent complication was respiratory distress, which was present at hospital admission in 4 patients and developed after admission in an additional 3 patients. P. knowlesi parasitemia at hospital admission was an independent determinant of respiratory distress, as were serum creatinine level, serum bilirubin, and platelet count at admission (P < .002 for each). Two patients with knowlesi malaria died, representing a case fatality rate of 1.8% (95% confidence interval, 0.2%–6.6%). Conclusions—Knowlesi malaria causes a wide spectrum of disease. Most cases are uncomplicated and respond promptly to treatment, but approximately 1 in 10 patients develop potentially fatal complications.